Estimation of serum C-reactive protein activity in periodontal health and disease and response to treatment: a clinico-biochemical study - Shahabe Saquib Abullais; Yogesh Wykole; Mohasin Abdul Khader; Shaik Mohamed Shamsudeen; Sultan Alanazi; Shafait Ullah Khateeb; Mohammad Yunis Saleem Bhat; Shaheen Shamsuddin (PeerJ, 2023)
Background Periodontitis is a chronic infectious disease affecting periodontium having multifactorial etiology, can cause significant systemic challengein addition to localized inflammation, tissue damage, and bone resorption. A serological marker of systemic inflammation known as C-reactive protein has been linked to an increased risk for a number of pathological conditions, including cardiovascular diseases. Aim To estimate levels of serum C-reactive protein in healthy individuals and subjects with periodontal diseases and to compare serum C-reactive protein levels in subjects having periodontal disease pre-operatively & post-operatively. Materials and methods The study was conducted on 60 subjects age ranging from 35 to 60 years. 30 individuals with healthy periodontium were in group 1 (control group) and the remaining 30 were diagnosed as adult periodontitis were in group 2 (experimental group). Periodontal examination done using gingival index, plaque index, periodontal pocket depth, and Russel’s index. CRP levels were examined between group 1 and group 2 and in group 2 between baseline visit before treatment and 2 months after treatment. Results The findings of this study show a significant connection between periodontal disease and the inflammatory marker CRP in the body, as well as a tendency for a significant decrease in serumCRP levels following periodontitis therapy. At baseline, there was a positive correlation among C-reactive protein, probing pocket depth, and Russell’s index. Conclusion As CRP is a key mediator for cardiovascular disease, an increase in C- reactive protein levels in periodontal diseases suggests a significant connection between periodontitis and cardiovascular diseases. Early periodontal treatment might decrease the severity of cardiovascular disease that already exists. This suggests that periodontal examination should be part of routine practicealong with cardiovascular examination.